Frequency in language memory, attention and learning - Divjak, Dagmar (Cambridge University Press, 2022)
"Cognitive linguists are bound by the Cognitive Commitment, which is the commitment to providing a characterization of the general principles governing all aspects of human language, in a way that is informed by, and accords with, what is known about the brain and mind from other disciplines. But what do we know about aspects of cognition that are relevant for theories of language? Which insights can help us build cognitive reality into our descriptive practice and move linguistic theorizing forward? This unique study integrates research findings from across the cognitive sciences to generate insights that challenge the way in which frequency has been interpreted in usage-based linguistics. It answers the fundamental questions of why frequency of experience has the effect it has on language development, structure and representation, and what role psychological and neurological explorations of core cognitive processes can play in developing a cognitively more accurate theoretical account of language"-- Provided by publisher.